2008
DOI: 10.1007/s00421-008-0849-9
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic exercise reduces tumor growth, cancer cachexia and increases macrophage and lymphocyte response in Walker 256 tumor-bearing rats

Abstract: Here, we investigated the effect of jump exercise on tumor growth, cancer cachexia, lymphocyte proliferation and macrophage function in Walker 256 tumor-bearing rats. Male Wistar rats (60 days) were divided into sedentary (C) and exercised (E) groups. Jump training consisted of six sets of 10 jumps in water with overload of 50% of body mass with 1 min of resting, four times per week for 8 weeks. After 6 weeks of training, half of each group was inoculated with 2 x 10(7) cells of Walker 256 tumor. Sedentary tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 43 publications
5
40
2
Order By: Relevance
“…The improvement of muscle depletion was associated with a small but significant decline in tumor burden in exercised, EPA-treated mice. This observation is consistent with previous data showing that PRT in Waker-256 bearing rats strongly reduced tumor growth [43], while swimming exercise attenuated colon carcinogenesis in the rat [44]. On the contrary, however, another study reported that tumorigenesis increased in p53-deficient mice exercised with a treadmill protocol similar to the one used in the present study [45].…”
Section: Discussionsupporting
confidence: 94%
“…The improvement of muscle depletion was associated with a small but significant decline in tumor burden in exercised, EPA-treated mice. This observation is consistent with previous data showing that PRT in Waker-256 bearing rats strongly reduced tumor growth [43], while swimming exercise attenuated colon carcinogenesis in the rat [44]. On the contrary, however, another study reported that tumorigenesis increased in p53-deficient mice exercised with a treadmill protocol similar to the one used in the present study [45].…”
Section: Discussionsupporting
confidence: 94%
“…It is well accepted that moderate-intensity exercise has an important influence on the immune system. [30][31][32] The link between exercise and the immune system includes the metabolic approach involving amino acid, carbohydrate, and lipid metabolism changes in the neuroendocrine system. 32,33 Furthermore, some studies have shown that lipid peroxidation and free radicals increase in humans and animals after physical activity.…”
mentioning
confidence: 99%
“…Walker 256 tumor-bearing rat offers an opportunity to investigate cancer cachexia and tumor growth due to its characteristics of inducing a higher level of cachexia in only 14 days Data are presented as mean ± SEM of 3 independent measurements [1]. A lot of diseases have been linked to lifestyle, diet, smoking and sedentary lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that exercise changes tumor progression [1,2] as well as improves wellbeing and quality of life of cancer patients [3,4]. These changes in tumor progression appear to be related to a process called lipid peroxidation (LP).…”
Section: Introductionmentioning
confidence: 99%